A Practical Approach to Managing Patients With Myasthenia Gravis—Opinions and a Review of the Literature - Farrugia, Maria Elena; Goodfellow, John A. (Frontiers in Neurology, 2020)
When the diagnosis of myasthenia gravis (MG) has been secured, the aim of management should be prompt symptom control and the induction of remission or minimal manifestations. Symptom control, with acetylcholinesterase inhibitors such as pyridostigmine, is commonly employed. This may be sufficient in mild disease. There is no single universally accepted treatment regimen. Corticosteroids are the mainstay of immunosuppressive treatment in patients with more than mild MG to induce remission. Immunosuppressive therapies, such as azathioprine are prescribed in addition to but sometimes instead of corticosteroids when background comorbidities preclude or restrict the use of steroids. Rituximab has a role in refractory MG, while plasmapheresis and immunoglobulin therapy are commonly prescribed to treat MG crisis and in some cases of refractory MG. Data from the MGTX trial showed clear evidence that thymectomy is beneficial in patients with acetylcholine receptor (AChR) antibody positive generalized MG, up to the age of 65 years. Minimally invasive thymectomy surgery including robotic-assisted thymectomy surgery has further revolutionized thymectomy and the management of MG. Ocular MG is not life-threatening but can be significantly disabling when diplopia is persistent. There is evidence to support early treatment with corticosteroids when ocular motility is abnormal and fails to respond to symptomatic treatment. Treatment needs to be individualized in the older age-group depending on specific comorbidities. In the younger age-groups, particularly in women, consideration must be given to the potential teratogenicity of certain therapies. Novel therapies are being developed and trialed, including ones that inhibit complement-induced immunological pathways or interfere with antibody-recycling pathways. Fatigue is common in MG and should be duly identified from fatigable weakness and managed with a combination of physical therapy with or without psychological support. MG patients may also develop dysfunctional breathing and the necessary respiratory physiotherapy techniques need to be implemented to alleviate the patient's symptoms of dyspnoea. In this review, we discuss various facets of myasthenia management in adults with ocular and generalized disease, including some practical approaches and our personal opinions based on our experience.